Simultaneous wireless information and GaN-based power transfer exploiting a dual frequency band - Placzek, J. Maximilian; Hoeher, Peter A.; Prasobhu, Pramod K.; Liserre, Marco; Buticchi, Giampaolo (2018)
A simultaneous wireless information and power transfer system employing separated frequency bands for energy and data, dubbed dual-band SWIPT, is investigated. Elementary circuit elements are optimized numerically. An experimental testbed based on a gallium nitride (GaN) full-bridge converter demonstrates data rates in excess of 450 kbps employing onoff keying in conjunction with a simple diode detector for data recovery.